Sistem Rekomendasi Tempat Makan Wilayah Solo Raya Berbasis Web dengan User Based Collaborative Filtering Menggunakan Fuzzy Conditional Probability Relation - Christian Suryadi; Rolly Intan; Hans Juwiantho (Jurnal Infra, 2021)
Recommendation system is a system used to predict an object for users in the form of useful information based on the rating value. Recommendation system can be applied for food places. The method commonly used for recommendation system is User-Based Collaborative Filtering. This method is a technique used to predict an item that the user likes based on the same rating, by means of user to user.This study uses User-Based Collaborative Filtering method using Fuzzy Conditional Probability Relation to perform calculations between users. Testing is done by calculating the accuracy of the recommendations generated by the system for users. The survey will be used to find the accuracy value of the method.The results of this study is the accuracy values from the User-Based Collaborative Filtering method using Fuzzy Conditional Probability Relation. Based on the survey results, the accuracy obtained is 62.78%, the accuracy using a rating limit of 2 is 47%, with a rating limit of 3 is 69%, and with a limit of 4 is 83%. From the results of this accuracy, we can summarize that User-Based Collaborative Filtering using Fuzzy Conditional Probability Relation can produce results that are quite good and satisfactory to provide recommendations.